Academic Supervision Based on Learning Management System in Improving Teacher Performance - Ningsih, Nelly Rahmawati; Suprananto; Suryaman, Maman; Wahyudin, Undang (LifeSciFi, 2025)
The digital transformation in educational institutions demands a more effective, well-documented, and technology-adaptive model of instructional supervision. This study aims to analyze the implementation of Learning Management System (LMS)-based academic supervision and its impact on teacher performance and instructional quality. Employing a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document analysis involving the principal, vice principal for curriculum, and teachers. The findings reveal that LMS-based supervision is systematically implemented through digital scheduling, instructional document uploads, classroom recording submissions, and direct feedback via LMS features. Digital supervision significantly enhances teacher discipline, administrative consistency, digital competence, and the quality of instructional planning. LMS also accelerates the feedback cycle and strengthens reflective teaching practices. However, several challenges emerge, including unstable internet connectivity, teacher psychological pressure, and difficulties in digital adaptation. LMS-based supervision positively contributes to instructional quality and supports school quality management. This study highlights the importance of integrating digital supervision into teacher professional development, particularly in vocational education settings.